2020
DOI: 10.3390/e22050520
|View full text |Cite
|
Sign up to set email alerts
|

Improving Accuracy of Heart Failure Detection Using Data Refinement

Abstract: Due to the wide inter- and intra-individual variability, short-term heart rate variability (HRV) analysis (usually 5 min) might lead to inaccuracy in detecting heart failure. Therefore, RR interval segmentation, which can reflect the individual heart condition, has been a key research challenge for accurate detection of heart failure. Previous studies mainly focus on analyzing the entire 24-h ECG recordings from all individuals in the database which often led to poor detection rate. In this study, we propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A large number of epidemiological trials have shown that LP-PLA2 is an independent factor for predicting CVE [ 22 ]. Scholars Xiong et al corrected the risk factors of traditional CVD and found that LP-PLA2 was still a risk predictor for CVE and had a positive correlation with the severity of CHF; e.g.,, the elevated level of CHF could increase the LP-PLA2 level [ 23 ]. In this study, no statistical differences in the enrolled patients' general information such as age and gender were observed ( P > 0.05), the serum LP-PLA2 levels were obviously different between the severe group and the mild group, and according to the logistic regression analysis, serum LP-PLA2 had independent predictive value for AHF prognosis, demonstrating that its level was of great importance in AHF and not just in CHD and CHF.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of epidemiological trials have shown that LP-PLA2 is an independent factor for predicting CVE [ 22 ]. Scholars Xiong et al corrected the risk factors of traditional CVD and found that LP-PLA2 was still a risk predictor for CVE and had a positive correlation with the severity of CHF; e.g.,, the elevated level of CHF could increase the LP-PLA2 level [ 23 ]. In this study, no statistical differences in the enrolled patients' general information such as age and gender were observed ( P > 0.05), the serum LP-PLA2 levels were obviously different between the severe group and the mild group, and according to the logistic regression analysis, serum LP-PLA2 had independent predictive value for AHF prognosis, demonstrating that its level was of great importance in AHF and not just in CHD and CHF.…”
Section: Discussionmentioning
confidence: 99%
“…While this method offers a well-defined information-based predictability assessment, it faces the fundamental problems that have arisen concerning data processing. Efforts for less demanding processing, especially of biologically relevant data, were subsequently reflected in the design of approximate entropy (ApEn) and later in the modified sample entropy variant (SampEn) [ 7 , 8 ]. Some of the shortcomings of these approaches have been addressed by the adjustments contained in the multiscale description (MSE) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%